First peoples [videorecording (DVD)] - Shale, Kerry (Wall to Wall Media Limited, 2015)
200,000 years ago we took our first steps in Africa. Today there are seven billion of us living across the planet. How did our ancestors spread from continent to continent? This is a global detective story, featuring the latest archaeological discoveries and genetic research. On each continent, we track down the earliest members of our species, Homo sapiens. Who were these First Peoples? What drove them to the ends of the earth?